Impact of COVID-19 lockdown on commuting: A multi-country perspective - Shibayama, Takeru; Sandholzer, Fabian; Laa, Barbara; Brezina, Tadej (European Journal of Transport and Infrastructure Research, 2021)
We carried out an international online survey about changes in everyday mobility during the COVID-19 outbreak in 21 languages, collecting more than 11,000 responses from more than 100 countries. In this paper, we present our analysis about commuting travels of the responses between 23 March and 12 May 2020 from the fourteen countries with 100 or more responses, namely Austria, Brazil, Bulgaria, Czechia, Germany, Hungary, Iran, Italy, Japan, Malaysia, Slovakia, Slovenia, Thailand, and the UK. Home office is used typically by between 40% and 60% of working respondents. Among people with workplaces with possibility for home office, the percentage is between 60% and 80%. Among people with workplaces where presence is essential, the percentage does not typically go beyond 30%. This result potentially implies an ultimate magnitude of a strong home office measure. Among those who continued to commute but switched commuting transport modes from public transport to others, the COVID-19 infection risk in public transport is the reason that is most often referred to, but many of those who changed to private cars and to bicycles report reduced travel time, too. Measures to encourage the use of active travel modes where possible are strongly recommended, as this would potentially mitigate undesirable modal shift towards private motorized modes triggered by perception of infection risks while travelling with public transport.